Analisa Strengths, Weaknesses, Opprotunities, and Threats (SWOT): Peluang dan tantangan Association of Southeast Asian Nations (ASEAN) dalam mewujudkan integrasi Asia Tenggara - Lilik Salamah (Faculty of Social and Political Science, Universitas Airlangga, 2017)
As a regional organization, ASEAN has grown dynamically, proven by the increasing number of members and areas of cooperation that have been pursued. Along with globalization, this success is increasingly encouraging the will to achieve integration in ASEAN VISION 2020. Through SWOT analysis of strengths (Strengths), Weaknesses, Opportunities and Threats (SWOT) and with the base of regionalism theory, this paper examines the creation of perspective of Southeast Asian integration. Through the framework and analysis of the problems, the results show that there are potential of ASEAN states to grasp the available international opportunity. This is also supported by existing policies in filling opportunities in economic, socio-culture, or politic security area. However, various problems still occured in realizing ASEAN integration. The main problem generally related to the sense of belonging of a person with the value of unity in diversity. Given the circumstances that exist both internally and among ASEAN member countries, presumably the idealism of the formation of integrity of Southeast Asia region is difficult to be realized.